Caspase Control: Protagonists of Cancer Cell Apoptosis - Fiandalo, M.V.; Kyprianou, N. (Experimental Oncology, 2012)
Emergence of castration-resistant metastatic prostate cancer is due to activation of survival pathways, including apoptosis suppression and anoikis resistance, and increased neovascularization. Thus targeting of apoptotic players is of critical significance in prostate cancer therapy since loss of apoptosis and resistance to anoikis are critical in aberrant malignant growth, metastasis and conferring therapeutic failure. The majority of therapeutic agents act through intrinsic mitochondrial, extrinsic death receptor pathways or endoplasmic reticulum stress pathways to induce apoptosis. Current therapeutic strategies target restoring regulatory molecules that govern the pro-survival pathways such as PTEN which regulates AKT activity. Other strategies focus on reactivating the apoptotic pathways either by down-regulating anti-apoptotic players such as BCL-2 or by up-regulating pro-apoptotic protein families, most notably, the caspases. Caspases are a family of cystine proteases which serve critical roles in apoptotic and inflammatory signaling pathways. During tumorigenesis, significant loss or inactivation of lead members in the caspase family leads to impairing apoptosis induction, causing a dramatic imbalance in the growth dynamics, ultimately resulting in aberrant growth of human cancers. Recent exploitation of apoptosis pathways towards re-instating apoptosis induction via caspase re-activation has provided new molecular platforms for the development of therapeutic strategies effective against advanced prostate cancer as well as other solid tumors. This review will discuss the current cellular landscape featuring the caspase family in tumor cells and their activation via pharmacologic intervention towards optimized anti-cancer therapeutic modalities. This article is part of a Special Issue entitled “Apoptosis: Four Decades Later”.